A piloted simulation investigation of several command concepts for transport aircraft in the approach and landing - Field, Edmund (Cranfield University, 1994)
With the introduction of modern fly-by-wire aircraft, the response of an aircraft to a pilot’s input can be augmented to something other than that for a conventional aircraft, with the resultant benefits and problems. The issue of what commanded response a pilot desires has received considerable attention, however no clear conclusions have yet emerged. The requirements for up and away flight and for the flare and landing seem to be different. Away from the ground rate command systems such as pitch rate and flight path rate seem to be well received for their low pilot workload associated with the control of flight path. However in the flare and touchdown these systems exhibit unnatural floating tendencies, requiring the pilot to push forward on the stick to land the aircraft. As a result most fly-by-wire aircraft incorporate separate up and away control laws and flare laws. This investigation is designed to consolidate on the work achieved by many organisations over the past ten years and concentrate on pilots’ preferences for the final stages of the approach and into the flare and touchdown. Twenty nine different flight control law configurations were designed for a regional sized aircraft. These configurations concentrated on several different command philosophies designed to investigate the pilots’ preferred command parameter and covered three different centre of gravity locations. These configurations were then implemented on the fixed base engineering simulator at British Aerospace Regional Aircraft, Hatfield, and evaluated by four test pilots.